A Cross-Platform Genome-Wide Comparison of the Relationship of Promoter DNA Methylation to Gene Expression - Plume, Jeffrey M.; Beach, S. R.; Brody, Gene H.; Philibert, Robert A. (Frontiers in Genetics, 2012)
Peripheral mononuclear cell preparations are commonly used as proxies for other tissues, such as brain, in studies of the role of gene expression and methylation in human disease. Using these materials, a number of investigators have demonstrated that alterations in DNA methylation are associated with autism, depression and other CNS disorders. Unfortunately, whether these changes in peripheral DNA methylation are associated with changes in peripheral blood gene expression is not clear. In order to examine this question and determine which genome wide methylation platform was most ideal for our studies of peripheral blood cells, we compared the results from two commercially available genome-wide methylation arrays with respect to genome wide gene expression using lymphoblast DNA and RNA from 8 individuals at 5,619 genes with promoter associated CpG islands. We found that methylation profiles from both platforms were significantly correlated with one another and genome wide gene expression, but the extent of that relationship is dependent on choice of platform and degree of methylation. Taken in context with data from other studies, these data demonstrate that peripheral blood cell methylation is associated with gene expression and that further studies to clarify the extent of this relationship, and the relationship between central and peripheral DNA methylation are in order.